Choreographic code of short stories by Volodymyr Korniychuk - Горболіс, Лариса (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
In the article on the material of the short stories «Chrysanthemum» (in the rhythm of the waltz), «Adducted Ksenia, abducted ...» (Semi-extravaganza in the rhythm of the tango), «Oleksa» (Tragedy polka on two sides), «We are Dancing”(In the rhythm of the incendiary hopak) by contemporary Ukrainian writer VolodymyrKorniychuk explores the specifics of the artistic embodiment of the choreographic material at different levels – genre, plot creation, mood-intonation, problem-thematic, visual, rhythmic, syntactic. Each work, taking into account the subtitles, has its own choreographic code, which reveals a hidden melodic line, emphasizes the event, marks the dynamic pattern of the piece in the appropriate sense. So, thanks to the dance (its motives) Volodymyr Korniychuk’s works are enriched with new psychological meanings, creating an original figurative model. The dance in short stories is implemented in various artistic and semantic formats. The waltz in «Chrysanthemums» drivesthe plot and is the culmination of the relations of heroes, an eloquent exponent of the characters’ feelings. Artistic mastering of the dance form of tango in the short story «Adducted Ksenia, Abducted ...»is a successful attempt of updating modern small prose by the author. The musical form of the polka is skillfully sustained in the work of «Oleksa»; the rhythmic pattern of the short story«We are Dancing» is more expressive with the help of verbal repetitions (fragments of rehearsal work with the children’s choreographic collective). Despite of the different aspects of the development of choreographic constructions, the original rhythm is common for short stories. An intermedial approach to the analysis of short stories by Volodymyr Korniychuk provides a diverse and deep reading of complex texts, where music and choreographic material is an organic component of a literary work, a means of characterizing the heroes, their complex world of feelings and emotions. Paratextuality sets the reader to a promising dialogue with the text, maximizes the decoding of choreographic indicators, verbalized in the text, which are rhythm, figures, tact, dramatic situation, tonality of interpersonal relationships of dance performers.